2018
DOI: 10.2147/opto.s167297
|View full text |Cite
|
Sign up to set email alerts
|

Visual performance of myopia control soft contact lenses in non-presbyopic myopes

Abstract: PurposeTo compare the visual performance of soft contact lenses reported to reduce myopia progression.MethodsIn a double-blind, randomized, crossover trial, 30 non-presbyopic myopes wore MiSight™, center-distance Proclear® Multifocal (+2.00 D add), and two prototype lenses for 1 week each. High- and low-contrast visual acuities at 6 m, and 70 and 40 cm; stereopsis at 40 cm; accommodative facility at 33 cm; and horizontal phoria at 3 m and 33 cm were measured after 1 week. Subjective performance was assessed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
63
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(68 citation statements)
references
References 33 publications
4
63
1
Order By: Relevance
“…Fedtke et al 39 reported that decentred multifocal contact lenses with higher power variations produce lower subjective ratings. Sha et al 25 found that two prototype lenses were tolerated better by non‐presbyopic myopes than the DF design lens used in the present study and another commercially available, centre‐distance multifocal contact lens. Wahl et al 31 noted that disability glare was higher with a centre‐distance contact lens than a centre‐near design.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Fedtke et al 39 reported that decentred multifocal contact lenses with higher power variations produce lower subjective ratings. Sha et al 25 found that two prototype lenses were tolerated better by non‐presbyopic myopes than the DF design lens used in the present study and another commercially available, centre‐distance multifocal contact lens. Wahl et al 31 noted that disability glare was higher with a centre‐distance contact lens than a centre‐near design.…”
Section: Discussionmentioning
confidence: 45%
“…Different studies have not reported significant differences in distance VA and stereopsis under light conditions between myopia control DF and SV contact lenses or spectacles 1,10,12,21 . Sha et al 25 found that the DF design used in the present study and a centre‐distance multifocal contact lens (Proclear Multifocal Dominant, http://www.coopervision.com) provided excellent high and low contrast VA at all distances. Similar outcomes were reported in the multicentre clinical trial by Chamberlain et al 10 …”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…[22][23][24] In terms of best corrected visual acuity (BCVA), MiSight has recently been shown to provide satisfactory visual acuity at both long and short distance. 25 Based on the above-mentioned facts, the present study consists of comparing the aberrations in the eyes of children randomly allocated to: 1) a control group using single-vision (SV) spectacles, and 2) a study group in which children wore a myopia control MiSight lens over a period of 24-months. The main objective of the study was to determine the differences between the ocular and corneal aberrations arising from the myopia progression in both control and study groups.…”
Section: Ocular and Corneal Aberrations Changes In Controlled Randomimentioning
confidence: 99%
“…By reducing hyperopic peripheral defocus and thus moving the peripheral image forward, possibly even creating myopic defocus, the stimulus for eye elongation is thought to be reduced. Visual performance with bi-and multifocal soft contact lenses was previously investigated in pre-presbyopic subjects with respect to the quality of vision [12][13][14] and changes in the accommodation behaviour 7,[15][16][17][18][19][20][21][22] . A recent investigation by Gong et al 23 showed that children fitted with centre-distance multifocal soft contact lenses with a positive addition of +2.5 D (Biofinity, comfilcon A, Cooper Vision) used the lenses' addition power during near vision to relax their accommodation.…”
mentioning
confidence: 99%